PREPARATION OF FUTURE PRIMARY SCHOOL TEACHERS FOR THE USE OF AUGMENTED REALITY IN LITERACY AND LITERARY READING LESSONS - Nezhyva, Liudmyla; Palamar, Svitlana (Educological discourse, 2021)
The article substantiates the urgency of the problem of preparation of future teachers to use AR technology in the language and literature field of primary education. Scientific sources on the problem of AR application in education are analyzed. Possibilities of using AR in work with younger students are considered. The specifics of interactive alphabets, coloring books, art books of Ukrainian and foreign writers, toys with AR-applications, which are appropriate to use in working with younger students, are characterized. A method of diagnostic research of the level of readiness of future teachers to use AR in the language and literature field of primary education has been developed. Criteria, indicators are defined, the levels of development of the main components of the studied readiness (motivational, cognitive, activity) are characterized. One has confirmed the insufficiency of its formation in future teachers in the field of primary education, inconsistency between the peculiarities of training future teachers to use AR in professional activities and modern requirements for the quality of the educational process, the need to develop and implement a holistic system of formation of the studied readiness of future teachers in terms of higher pedagogical education. A model of forming the readiness of future teachers to use AR in the language and literature field of primary education has been developed. The main tasks are defined as follows: to form teachers’ motivation, understanding of the importance of using augmented reality technology in professional activities, to expand and deepen students’ knowledge about the specifics of AR, the variety of educational tools with AR applications, to promote the mastery of techniques for working with teaching aids with AR, ways to organize junior high school students when working with AR applications. The model contains the following stages: cognitive (research of scientific sources, analysis of curricula and work programs of academic disciplines of pedagogical institutes, study of the current state of readiness of future teachers to use AR in professional activities), activity (development of the semantic module "Fundamentals of AR application in the linguistic and literary field of primary education"), creative (development of master classes, trainings, webinars, quests on the problem of application of augmented reality technology in the linguistic and literary field of primary education).